(untitled) (Revista da Faculdade de Odontologia - UPF, 2013)
Introduction: the latex biomembrane BiomembranaTM has been used in several medical specialties with promising results in promoting wound healing, including surgical, traumatic, isquemic and pressure-induced, as well as ulceration of varied etiology. However, in dentistry its use is not currently well established. Objective: the aim of this study was to describe a treatment for vestibuloplasty using a latex membrane. Case report: due to the inherent characteristics of the latex biomembrane (BiomembranaTM), a vestibuloplasty of the anterior sextant of the mandible was performed using Arruda’s technique of second intention healing modified by the use of a latex biomembrane, in order to assess its applicability and ability to maintain the depth of the vestibule in this type of surgery. Final considerations: latex membrane is an easy to use material which proved useful for vestibuloplasty, since it provided gain of attached gingiva, which remained stable during the 9-month follow-up period.